Madeline Sewepagaham interview - Sewepagaham, Madeline; Nanooch, Roger (Canadian Plains Research Centre, 1978)
4 p. transcript of an interview with Madeline Sewepagaham, conducted by Roger Nanooch in August of 1978. Tape number IH-322, transcript disc 29. Born at Treaty #8 signing, this interviewee speaks about Wood Buffalo National Park, and the impact on trapping and hunting in the area. Other no